Perceived Message Effectiveness and Campaign-Targeted Beliefs: Evidence of Reciprocal Effects in Youth Tobacco Prevention. Issue 3 (23rd February 2022) - Zhao, Xiaoquan; Delahanty, Janine C.; Duke, Jennifer C.; MacMonegle, Anna J.; Smith, Alexandria A.; Allen, Jane A.; Nonnemaker, James
ABSTRACT: Perceived message effectiveness (PE) has been widely used in campaign formative research and evaluation. The relationship between PE and actual message effectiveness (AE) is often assumed to be causal and unidirectional, but careful conceptualization and empirical testing of this and other causal possibilities are generally lacking. In this study, we investigated the potential reciprocity in the relationship between PE and AE in the context of a national youth tobacco education campaign. In so doing, we also sought to generate much needed evidence on PE's utility to predict campaign-targeted outcomes in youth tobacco prevention. Using five waves of campaign evaluation data (N = 1, 128), we found significant lagged associations between PE and campaign-targeted beliefs, and vice versa. These results suggest a dynamic, mutually influencing relationship between PE and AE and call for greater attention to such dynamics in campaign research.